Sex-related differences in outcome of thoracic aortic surgery - Hongxue Jiang; Hongjie Xu; Zhiyun Xu (Journal of Cardiothoracic Surgery, 2024)
Abstract Background Sex-related dissimilarities’ influence on outcomes following thoracic aortic surgery is poorly understood. Our aim is to examine sex-related disparities in patients undergoing thoracic aortic aneurysm (TAA). Methods A total of 455 cases undergoing thoracic aortic aneurysm (TAA) surgery were consecutively enrolled between December 2009 and December 2015 in a Chinese hospital. Primary outcomes, including overall mortality and related risk factors, were evaluated. Cox regression is utilized to recognize the independent risk factor of these consequences. Results Females, compared to males, had greater indexed aortic diameters and higher aortic transvalvular pressure differences. For the location of aortic aneurysms, females had a higher rate of aortic arch involvement, while males had a higher rate of root involvement. Females underwent less frequent complex proximal aortic operations compared with males (29.5% versus 46.9%; p < 0.001). Women and men both had a lower rate of aortic transvalvular pressure difference and LV volume index 7 days after thoracic aortic surgery. The overall mortality for the women’s groups (11%) was suggestively greater compared to 4.9% for the men’s groups (p = 0.026). Renal failure and aortic arch involvement were the main risk factors associated with males’ survival, while maximum indexed aortic diameter and cross-clamp time were the risk factors associated with females’ survival. Conclusions The outcome after TAA surgery was less favorable in women with significantly increased overall mortality. It highlights the need to focus on implementing personalized surgery strategies and gender-specific guidelines in treating female patients following TAA surgery.